LA PHILOSOPHIE EN ACTION AUPRÈS D’ADOLESCENTS DYSFONCTIONNELS : RENFORCER LA RÉSISTANCE PRÉPARER LA RÉSILIENCE À L’AIDE DE LA MATRICE DIDACTIQUE DE MICHEL TOZZI - HENRION-LATCHE, Johanna (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Philosophy in Action with Dysfunctional Adolescents: Strengthening Resistance, Preparing Resilience Using Michel Tozzi’s Teaching Matrix. Our contribution is based on research conducted with dysfunctional teenagers, prevented from thinking, in a praxis of resilience assisted by philosophical discussion according to the method of Michel Tozzi. A good distance from a process of modelling thought, it’s question of articulating the process of accompaniment the young person’s by Michel Tozzi didactic model. Based on anthropologically situated discussions in the interrogations of adolescents put into play by means of written materials according to Mathew Lipman’s recommendations, the philosophical discussions method’s that we submit is intended to guide educators to explore the process that hinder the activity of thinking and to engage teenagers in a process of rebounding from their own arguments. We present our method which aims at equipping teenagers with the proper tools of resistance to adversity and resiliency in the face of harmful experiences.